PENGEMBANGAN MEDIA PEMBELAJARAN AKSARA JAWA BERBASIS SCRABBLE UNTUK MENINGKATKAN KEMAMPUAN MENULIS SISWA KELAS IV SDN NGEBELGEDE 1 - dea arini; arini, dea (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Learning to write Javanese texts has not been promoted because there are obstacles starting from the lack of different learning methods and media, which makes it difficult for students to write scripts and sandhangan because the style and pronunciation are the same. The purpose of the research to develop a skillful, efficient and effective Scrabble-based Javanese written language learning to facilitate the learning of the Javanese language, text writing and improve writing skills in students of the fourth grade at SDN Ngebelgede I. This development uses the 4-D (four-D) model. it has 4 stages namely Definition, Design, Development and Dissemination. Data collection methods use observations, interviews, questionnaires, tests and documents. The data analysis method makes use of qualitative analysis in the form of advice and input from experts, as well as quantitative analysis obtained from statistical analysis in the form of questionnaires and tests. The result of the emphasis on the material in the media received an average value of 4.8 with a very strong component. The media confirmation result is the result of an average of 4.5 real parts. The results of the teacher's answers reached an average of 4.8 points in the specific skill category. The results of the students' answers to the short test received a score of 4.12 in the functional category and the results of the field test received a score of 4.33 in the category of specific skills. Scrabble-based learning media for writing the Javanese script is also effective in improving writing skills according to the student's academic average. There is a difference shown by the mean value of the last paired sample T-test producing Sig. (2-tailed) 0.000 < 0.05 with a mean pretest score of 47.27 and a mean posttest score JURNAL PERSEDA VOL. VII, NO. 3, DESEMBER 2024 | 290 of 82.27, an increase of 35.00. It can be concluded that Scrabble-based javanese script learning media is effective in improving Javanese script writing skills.